Some Euler-Maclaurin-Type Inequalities by Means of Tempered Fractional Integrals (Journal of Nonlinear Modeling and Analysis, 2024)
This paper introduces an equality that is valid for tempered fractional integrals. By using this equality, we establish some Euler-Maclaurin-type inequalities for the case of differentiable convex functions involving tempered fractional integrals. Furthermore, our results are provided by usingspecial cases of obtained theorems.
Keywords: Euler-Maclaurin-type inequality; quadrature formulae; tempered fractional integrals; convex functions.